Super-refraction over west coast off Bombay - KUMAR, S.; KISHAN, DAYA; KRISHNAMURTHY, G. (MAUSAM, 1976)
The echoes observed in absence of any-clouds over- west coast off Bombay, during March-April 1974 are due to the super-refraction of the radar waves in the lower layers of atmosphere over the sea. These were found to occur whenever the sum of the ratios of the actual lapse rates of specific humidity and potential temperature to their critical values (for the occurrence of super-refraction) was unity or more. It is suggested that sea breeze circulation is mainly responsible for the formation of these echoes over west coast off Bombay during hot weather period. The movement of the echoes, their intensity, distance from the station and their multiplicity have been correlated with the development, type and strength of the sea breeze circulation.